Strategi Pemasaran Perguruan Tinggi Swasta - Setyawan Setyawan (Akutansi Bisnis & Manajemen ( ABM ), 2015)
Competition between private colleges need to be managed properly and professionally as like as company profits. Recruiting new students competition is more difficult, with limited resourcess support. Marketing strategy of private college is a set of policies and rules that give direction in managing marketing in an integrated by considering internal and external conditions. The marketing strategy drawn with regard to existing conditions, SWOT analysis, organizing, and controlling at STIE Malangkucecwara which is based on the Standard Quality of Education (accredited): Service Quality Management (Quality Assurance), condition and reputation of the college, coordinate and integration on the task and marketing efforts with other unit / operational area, begins by creating an integrated plan, such as: student activities, faculty research done to be published on a regular basis, which raises the image quality of the campus to the community. Efforts to monitor the implementation of marketing strategies related to the achievement of performance targets an increase in the number of applicants, including the re-registration, achievement of the activities of external and internal marketing activities.